Do Different Levels of Management Impact Employee Intrapreneurial Behavior Independently? A Multi-Mediation Analysis - Wasim Abbas Awan; Mahrukh Askari; Hina Amin (iRASD Journal of Management)
Emerging trends and economic growth have given managers possibilities while posing challenges to conventional management practices. Managers must develop innovative approaches to coping with these difficulties. They may be able to overcome new obstacles and foster a creative workplace where workers are inspired to come up with fresh ideas with the aid of these new ways of working. Thus, enabling intrapreneurial conduct. This study looks at the characteristics that new ways of working create to drive employees to engage in intrapreneurial conduct, as mediated through social interaction and transformational leadership. Collecting a sample of 300 respondents from the informational technology industry, this study tested a multi-mediation model using PLS-SEM. The study concluded that combined social interaction and transformational leadership partially mediates the relation between new ways of working and employee intrapreneurial behavior. The study also focused on the moderating role of each management level and found that middle-level management foster employee intrapreneurial behavior stronger than first and top level. This study further paves the way for practitioners and researchers by presenting implications and providing future directions.